2016
DOI: 10.1161/circinterventions.115.003518
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Internal Thoracic Artery Configuration for Coronary Artery Bypass Surgery

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 18 publications
(21 reference statements)
0
25
1
3
Order By: Relevance
“…It has been shown that an increase in the number of BITA anastomoses is associated with better clinical outcome. 49 For DSWI, the adoption of the skeletonized technique for harvesting was similar between high and low BITA users (42.9% in the first quartile and 57.1% in the fourth quartile; P=0.56), and the association between the OR for DSWI and % BITA was confirmed, even in the multivariable meta-regression model after adjusting for skeletonization. These results suggest that BITA skeletonization alone is not the explanation for the reported difference in DWSI.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It has been shown that an increase in the number of BITA anastomoses is associated with better clinical outcome. 49 For DSWI, the adoption of the skeletonized technique for harvesting was similar between high and low BITA users (42.9% in the first quartile and 57.1% in the fourth quartile; P=0.56), and the association between the OR for DSWI and % BITA was confirmed, even in the multivariable meta-regression model after adjusting for skeletonization. These results suggest that BITA skeletonization alone is not the explanation for the reported difference in DWSI.…”
Section: Discussionmentioning
confidence: 75%
“…It is notable that 67% of the studies in the highest quartile of %BITA versus 38% in the lowest quartile used BITA sequentials ( P =0.03). It has been shown that an increase in the number of BITA anastomoses is associated with better clinical outcome …”
Section: Discussionmentioning
confidence: 99%
“…Glineur et al performed a prospective randomized trial that showed that the graft patency of BIMA grafts was similar between in-situ and Y-grafting coniguration, whereas the use of BIMA in a Y-grafting coniguration was associated in lower rates of major adverse cardiovascular and cerebrovascular events [45].…”
Section: Rationale For Bima Usementioning
confidence: 99%
“…In a recent prospective, randomized clinical trial, Glineur and colleagues 6 showed that the clinical benefit of the bilateral internal thoracic artery composite Y configuration seems independent of the quality of revascularization provided by the internal thoracic artery graft itself, but rather is related to the poor long-term outcome of the third complementary graft, more frequently needed with the in situ bilateral internal thoracic artery configuration. This implies that the quality of surgical revascularization could be optimized either by decreasing the number of coronary arteries that require a complementary third graft or by using as complementary third graft a conduit of superior quality.…”
mentioning
confidence: 99%
“…Composite bilateral internal thoracic artery grafting resulted in significant lower rates of major adverse cardiac and cerebrovascular events at 7 years than did conventional in situ bilateral internal thoracic artery grafting. 6 If surgical revascularization aims to remain the superior treatment in coronary artery disease, efforts should be made toward a more efficient use of internal thoracic arteries, reduction of the need for a third complementary graft, and identification of the best alternative to SVG as the third graft material for complete revascularization of multivessel disease. 7…”
mentioning
confidence: 99%